Low-temperature redetermination of 3,4,5,6-tetra-hydro-pyrimidin-2(1H)-one. - Rizal, M.R.; Azizul, I.; Ng, S.W. (International Union of Crystallography, 2008)
The low-temperature structure of the title compound, C(4)H(8)N(2)O, is ordered, whereas the central methyl-ene groups is disordered in the reported room-temperature structure. The molecule lies across a mirror plane; adjacent mol-ecules are linked by an N-H⋯O hydrogen bond into a chain.